Experimental, modeling and RSM optimization of CO2 loading for an aqueous blend of diethylenetriamine and 3-dimethyl amino-1-propanol - Gupta A.K.; Gautam A.; Mondal M.K. (My University, 2025)
Post-combustion CO2 capture by aqueous amine solvent is one of the most promising methods for mitigating the presence of CO2 in the environment. In this work, a novel amine blend of Diethylenetriamine and 3-Dimethyl amino-1-propanol was selected. Experiments were performed in the temperature range of 293.15–323.25 K, mole fraction of diethylenetriamine in the range of 0.05–0.2, partial pressure of CO2 in the range of 10.13–25.33 kPa and solution concentration in the range of 1–3 mol·L−1. Effects of these parameters on equilibrium CO2 loading were judged at various operating conditions. An empirical model was developed for the calculation of equilibrium CO2 loading in the aqueous amine blend. The heat of absorption of CO2 for this amine blend was found to be −65.22 kJ·mol−1. Response surface methodology (RSM) was used for optimization and a quadratic model was selected. The analysis of variance was used to prove the significance of the selected model. Three-dimensional diagrams and contour plots of independent variables were also shown. Optimum CO2 loading by RSM was found to be 1.068 mol CO2·mol amine−1 at temperature 294.15 K, mole fraction of diethylenetriamine 0.20, solution concentration 1.3 mol/l, and partial pressure of CO2 24.22 kPa. © 2023, The Korean Institute of Chemical Engineers.